Acute kidney injury and nephrotic syndrome associated with eltrombopag therapy in chronic idiopathic thrombocytopenic purpura. Issue 4 (7th April 2021) - Ghosh, Suchi Anindita; Patrick, Jean; Maw, Kyaw Zin
Abstract : A 77-year-old man was admitted with severe acute kidney injury and nephrotic syndrome. He was started on eltrombopag for chronic idiopathic thrombocytopenic purpura 6 weeks earlier. An ultrasound of the kidneys was normal and an auto-antibody screen was negative. The use of the Naranjo adverse drug reaction probability scale indicated a probable relationship (score of 5) between the patient's development of acute renal failure and eltrombopag therapy. Literature review identified only one other case of nephrotic syndrome and acute kidney injury associated with eltrombopag therapy in which a kidney biopsy revealed focal segmental glomerulosclerosis. Due to the challenges faced during the prevailing SARS-CoV-2 pandemic and persistent low platelet counts a renal biopsy was not undertaken. On stopping eltrombopag, the patients renal function stabilised and he successfully went into remission following treatment with high dose corticosteroids and diuretics. This report of a serious case of reversible renal failure and nephrotic syndrome after treatment with eltrombopag may serve to inform clinicians about the possible severe renal adverse effects of eltrombopag before its commencement for future use.